Market information and access to structured markets by small farmers and traders: Evidence from an action research experiment in central Malawi: Synopsis - Ochieng, Dennis O.; Botha, Rosemary; Baulch, Bob (International Food Policy Research Institute, 2020)
Structured markets are organized platforms where economic agents such as farmers, traders, processors and financial institutions enter transparent and legal trading and financial arrangements (East Africa Grain Council 2013). Structured markets are important for the stabilization of volumes and prices of agricultural commodities (Hernandez et al. 2017) and diversification of foreign exchange earnings (Edelman et al. 2014). If supported by export mandates, structured markets for cereals and legumes could also limit informal cross-border trade and increase agricultural exports (Government of Malawi 2016). They could potentially also provide better statistics on volumes traded to aid in the planning, production, and marketing of crops in Malawi (Baulch and Gondwe 2017).